Public agricultural R&D investments and capacities in developing countries: Recent evidence for 2000 and beyond - Beintema, Nienke M.; Stads, Gert-Jan (International Food Policy Research Institute, 2010)
Compiling up-to-date, accurate information on global trends in public agricultural R&D investments is extremely challenging because for many countries no such information exists, and for others the available information is outdated, irregular, or incomplete. The Agricultural Science and Technology Indicators (ASTI) initiative strives to redress this problem, but—as a public good—ASTI focuses on developing countries (herein defined as low- and middle-income countries). In addition, based on financial and time constraints, ASTI collects data on a regional basis and over considerable intervals of time.